Residue of Aflatoxin and Its Metabolites on Various Animal Products and Its Prevention - Widiastuti, Raphaella (Indonesian Bulletin of Animal and Veterinary Sciences, 2014)
Aflatoxins especially aflatoxin B1 is mycotoxins that must be concerned. When consumed by livestock, it becomes aflatoxin M1 and other metabolites in animal products that harmful for public health. This paper provides information of aflatoxins residues and their metabolites in a variety of animal origin food (milk, meat and eggs) and the prevention of their occurrence. Aflatoxin residues were found in a variety of livestock and dairy products in various countries including Indonesia. Due to its stability in any processing or storage methods, preventing aflatoxins enter the food chain is essential. Implementing the regulatory limits for aflatoxins in feed and food should be made to avoid further effect on human health. Information and extensive monitoring of aflatoxins should be carried out not only in milk but also in many different types of animal products (buffalo, quail, sheep and goat), as the data in Indonesia is not yet available. Key words: Residue, aflatoxins, animal products, prevention